Caracterización geológico - geotécnica de los taludes presentes a lo largo de la vía el Carmelo _ Lauro Guerrero a nivel de factor de seguridad, ubicado en la parroquia Lauro guerrero del cantón Paltas, provincia de Loja. - Alvarado Pullaguari, María Fernanda (2023)
The objective of this work is to carry out a study of the slopes and the landslides that occurred along the Carmelo - Lauro Guerrero road, from abscissae 0+000 to 7+661 in the Paltas canton of the province of Loja, focused on the geological-geotechnical characterization, specifically designed to understand the lithological characteristics, physical-mechanical characteristics of the geomaterials and safety factor. We started with the geological description of the study area based on topography and through in situ reconnaissance techniques, we were able to identify the critical areas to be analyzed. Then, we proceeded with the collection of samples from both the test pits and the slopes for the respective laboratory tests. To determine the physical-mechanical properties of the geomaterials, information was obtained from two direct shear tests and eight soil classification tests according to ASTM D2487 standards. In addition, two vertical electrical soundings and a seismic line were used at strategic points on the slopes in order to corroborate the geology and obtain the properties of the geomaterials. For the rock masses, a simple compression test was performed. As for the physical properties, a specific gravity test of solids was carried out in accordance with ASTM D854-58. The geomechanical classification of the rock masses was carried out according to RMR, SMR, Q and GSI, thus allowing the characterization of the slopes and the determination of their stability. In the general stability analysis, the calculation of the safety factor consisted of performing simulations using Slide 6.0 software, with geometric and geotechnical parameters by means of the limit equilibrium method (Bishop, Spencer and Janbu), the analysis was performed for seismic and static loads under existing conditions. Keywords: slope, geomaterials, geomechanical classification, rock mass, safety factor.